Litho-facial models of Pirallahi field’s oil deposits on geophysical well logging data - L. F. Shikhova (Геофизический журнал, 2017)
Performed work aims to recreate the formation conditions of the basic lithotypes of geological section and construction of petrophysical models of medium on several horizons of Productive series on the basis of processing and interpretation of geophysical well logging data. By separating the geological section into lithofacies intervals, the data of geophysical investigations of more than 470 wells, including such well log data as apparent resistivity and spontaneous polarization has been used. The definition of electrometric models produced by the αsp curve values, i. e., ratio of SP curve to its maximum, which made it possible to reconstruct the paleogeographic setting and restore the genesis of sediments. It was determined that river channels have very good reservoir properties. During formation of the lower division of Productive series  two transgressive stages have been distinguished in the research area. The main variation regularities of petrophysical parameters of the medium have been revealed in three-dimensional space, consideration of which will allow us to create more effective models for further exploitation of Pirallahi field.